HUBUNGAN MOTIVASI KERJA PERAWAT DENGAN PELAKSANAAN PENDOKUMENTASIAN PROSES KEPERAWATAN DI RUANG RAWAT INAP RSUD SEKARWANGI - Indah Kirana, Adila (Jurnal Ilmu Psikologi dan Kesehatan (SIKONTAN), 2023)
Documentation is a written communication that permanently documents various information relevant to various patient health settings. Documentation is also a valid and legal record related to patient examination, diagnostic process, planning, implementation and evaluation process. The research design used is descriptive correlational with a cross sectional approach. The research population is the nurses who work in the Inpatient Room of Sekarwangi Hospital. The number of research samples is 65 respondents. Assessing the work motivation of nurses, most of the respondents were in the good category, 42 respondents with a percentage (64.6%) and for documentation, most of the respondents were in the good category, 49 respondents with a percentage (75.4%). From the results of the chi-square test, P value was obtained: 0.004 <0.05, where it can be concluded that there is a relationship between the work motivation of nurses and the implementation of nursing process documentation in the inpatient room of Sekarwangi Hospital. There is a relationship between the work motivation of nurses and the implementation of nursing process documentation in the Inpatient Room of Sekarwangi Hospital.